2004
DOI: 10.1038/sj.cdd.4401479
|View full text |Cite
|
Sign up to set email alerts
|

The topoisomerase 1-interacting protein BTBD1 is essential for muscle cell differentiation

Abstract: DNA topoisomerase I (Topo1) contributes to vital biological functions, but its regulation is not clearly understood. The BTBD1 protein was recently cloned on the basis of its interaction with the core domain of Topo1 and is expressed particularly in skeletal muscle. To determine BTBD1 functions in this tissue, the in vitro model used was the C2C12 mouse muscle cell line, which expresses BTBD1 mainly after myotube differentiation. We studied the effects of a stably overexpressed BTBD1 protein truncated of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…7, 8, 9, 21 As previously reported, 7, 8, 9 the L6 and C2C12 myotube formation is accompanied by upregulation of a number of genes including MyoD1 , myogenin and GLUT4 . Unexpectedly, however, these same gene profile studies revealed that expression of the autophagy regulator PED/PEA-15 underwent progressive reduction both during L6 and C2C12 cell differentiation (Figure 1a, left panel).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…7, 8, 9, 21 As previously reported, 7, 8, 9 the L6 and C2C12 myotube formation is accompanied by upregulation of a number of genes including MyoD1 , myogenin and GLUT4 . Unexpectedly, however, these same gene profile studies revealed that expression of the autophagy regulator PED/PEA-15 underwent progressive reduction both during L6 and C2C12 cell differentiation (Figure 1a, left panel).…”
Section: Resultsmentioning
confidence: 57%
“…These include BECLIN1, ATG8, Gabarapl1, ATG12, ATG4B and VSP34. 21, 22, 23, 24 FoxO1, in turn, is highly regulated at the post-transcriptional level. Dephosphorylation at Ser256 by the Ser/Thr phosphatase PP2A activates FoxO1, inducing its nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…BNC1 is involved in cell proliferation, and defective cell proliferation and migration in the PPFs of the developing diaphragm have been proposed to underlie CDH . Given the musculature of the diaphragm, BTBD1 is an interesting candidate involved in myoblast growth and differentiation …”
Section: Discussionmentioning
confidence: 99%
“…At 70%-80% confluence, cells were transfected with 4 lg of plasmids carrying the Luc reporter gene (PL-Luc) or equimolar 2 lg of MC carrying the Luc reporter gene (MC-Luc), using Lipofectamine 2000 (Invitrogen) according to the manufacturer's protocol. C2C12 cells show rapid proliferation with a doubling time of approximately 19 hr in vitro (Pisani et al, 2004). In order to more closely resemble the in vivo conditions of slower proliferating cells, C2C12 cells were exposed to 9,000 rad 3 hr before transfection, resulting in an optimal proliferation pattern (Supplementary Fig.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%